PENGARUH TEKNIK INSIDE OUTSIDE CIRCLE TERHADAP KEMAMPUAN KONSEP HURUF ABJAD PADA ANAK USIA 4-5 TAHUN (Studi Quasi- Eksperimental Di TK Negeri Pembina Kabupaten Serang) - Ina Listiani (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
Ina Listiani.NIM 211260006. 2025. The Effect of Inside Outside Circle Technique on Alphabet Concepts at Age 4-5 Years (Quasi-Experimental Study at Pembina State Kindergarten, Serang Regency) This study aims to determine the effect of the Inside-Outside Circle technique on the ability to conceptualize alphabet letters, especially vowels, in children aged 4-5 years at Pembina State Kindergarten, Serang Regency. The background of this study is based on the importance of recognizing vowels as a basis for early literacy skills, but there are still children who have difficulty in distinguishing and pronouncing vowels correctly. The benefits of this study include theoretical benefits as a contribution to the development of cooperative learning theory for early childhood, as well as practical benefits for children, teachers, schools, and researchers in designing more interactive and enjoyable learning. The study used a quantitative approach with a quasi-experimental method. The subjects of the study consisted of two classes, namely the experimental class using the Inside-Outside Circle technique and the control class using conventional methods. The data collection technique used pretest and posttest, while data analysis used N-Gain test and Mann Whitney test with the help of SPSS version 25. The results showed that there was a significant difference between the experimental group and the control group. The Mann Whitney test produced a significance value of 0.000 <0.05 and a Zcount value of -4.690, which means Ha is accepted and Ho is rejected. In addition, the average value of N-Gain Score in the experimental class of 52.69% indicates that the Inside-Outside Circle technique is quite influential in improving the ability to recognize vowels in children aged 4-5 years.